The Roles of Intensive and Extensive Reading Activities in Chinese EFL University Students’ Reading Comprehension Skills - Fu, Sijing (Education and Linguistics Research, 2024)
This paper focuses on the appropriate methods for Chinese EFL university students to improve reading comprehension skills. The combination of intensive reading and extensive reading in the teaching environment is suggested in this study. Specifically, in-class reading should be composed of two parts: 1) intensive reading activities involving the explicit instruction of reading comprehension skills; 2) extensive reading activities to increase Chinese EFL university students’ background and vocabulary knowledge, which paves way for the comprehension of the text. After-class extensive reading should be composed of the reading of materials containing the repetition of new vocabulary appear in class, which could consolidate EFL learners’ reading comprehension skills they have already learnt in class.